A pseudo-ELISA based on molecularly imprinted nanoparticles for detection of gentamicin in real samples. Issue 19 (5th May 2017) - Tang, Si-Ping; Canfarotta, Francesco; Smolinska-Kempisty, Katarzyna; Piletska, Elena; Guerreiro, Antonio; Piletsky, Sergey
Abstract : In this work, molecularly imprinted nanoparticles are used as direct replacement of antibodies in a pseudo-ELISA format (competitive assay) for detection of gentamicin in spiked milk. Abstract : The enzyme-linked immunosorbent assay (ELISA) is one of the most widely employed tests in diagnostics, and it relies on the use of antibodies to quantify the molecule of interest. Molecularly imprinted nanoparticles (nanoMIPs), thanks to their stability, cost efficiency and easy production, are a promising alternative to antibodies in assays and sensors. In this work, nanoMIPs have been produced by means of a solid-phase approach and employed for the detection of gentamicin in real samples. The produced nanoMIPs were characterized using dynamic light scattering (DLS) and transmission electron microscopy (TEM) techniques. The determination of gentamicin in spiked milk was implemented through an assay similar to enzyme-linked immunosorbent assay, in which the nanoMIPs were used as a synthetic capture antibody (pseudo-ELISA). The detection of gentamicin was achieved in competitive binding experiments with a horseradish peroxidase–gentamicin conjugate. Gentamicin was determined in milk at clinically relevant concentrations with a mean accuracy of 94%. The cross-reactivity of such nanoparticles was investigated with streptomycin and ampicillin as control antibiotics, demonstrating excellent specificity.